Clarification of the Definition of Business Reputation in Legal Science - Yu. V. Yachmenev; M. V. Kibenko (Теоретическая и прикладная юриспруденция)
This article proposes a precise definition of the concept of “business reputation”, presents various points of view of lawyers on business reputation. Business reputation is considered as a public assessment acquired in the course of professional, entrepreneurial or other socially significant activities, and the qualities inherent in this activity, a general or widespread opinion about the business qualities, merits of an individual or legal entity. The following methods were used in the study: analysis, comparison, concretization, generalization, study of scientific and legal literature and legal acts.